Level of anxiety and dental pain at different times in root canal treatment during the COVID-19 pandemic - Alcalde Picho, Carlos Ismael (2024)
Objective: To evaluate the level of dental anxiety (DA) and dental pain (DD) at different times in root canal treatment during the COVID-19 pandemic. Materials and methods: Observational, descriptive, and longitudinal study. The sample consisted of 68 participants from the Stomatology Clinic of the Hospital Militar Central (HMC), who met the inclusion and exclusion criteria. The procedure consisted of recording the level of AD and DD of the patients at different times during root canal treatment using a visual analog scale (VAS). Results: Before the procedure, participants showed 3.66±1.83 of AD and 4.54±1.79 of DD; during the procedure, they obtained values of 3.13±1.96 and 2.09±1.39 of AD and 2.96±1.57 and 1.82±1.09 of DD; and at the end of the procedure, they had 0.75±0.74 of AD and 0.53±0.72 of DD. Conclusions: AD and DD were found to be present before starting treatment, but as the procedure progressed their levels decreased.